Nanodots of Transition Metal Sulfides, Carbonates, and Oxides Obtained Through Spontaneous Co-Precipitation with Silica - Bastian Rödig; Diana Funkner; Thomas Frank; Ulrich Schürmann; Julian Rieder; Lorenz Kienle; Werner Kunz; Matthias Kellermeier (Nanomaterials)
The controlled formation and stabilization of nanoparticles is of fundamental relevance for materials science and key to many modern technologies. Common synthetic strategies to arrest growth at small sizes and prevent undesired particle agglomeration often rely on the use of organic additives and require non-aqueous media and/or high temperatures, all of which appear critical with respect to production costs, safety, and sustainability. In the present work, we demonstrate a simple one-pot process in water under ambient conditions that can produce particles of various transition metal carbonates and sulfides with sizes of only a few nanometers embedded in a silica shell, similar to particles derived from more elaborate synthesis routes, like the sol–gel process. To this end, solutions of soluble salts of metal cations (e.g., chlorides) and the respective anions (e.g., sodium carbonate or sulfide) are mixed in the presence of different amounts of sodium silicate at elevated pH levels. Upon mixing, metal carbonate/sulfide particles nucleate, and their subsequent growth causes a sensible decrease of pH in the vicinity. Dissolved silicate species respond to this local acidification by condensation reactions, which eventually lead to the formation of amorphous silica layers that encapsulate the metal carbonate/sulfide cores and, thus, effectively inhibit any further growth. The as-obtained carbonate nanodots can readily be converted into the corresponding metal oxides by secondary thermal treatment, during which their nanometric size is maintained. Although the described method clearly requires optimization towards actual applications, the results of this study highlight the potential of bottom-up self-assembly for the synthesis of functional nanoparticles at mild conditions.